2018
DOI: 10.12659/msm.907578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hexadecyl Azelaoyl Phosphatidylcholine on Cardiomyocyte Apoptosis in Myocardial Ischemia-Reperfusion Injury: A Hypothesis

Abstract: Reperfusion after myocardial ischemia can induce cardiomyocyte death, known as myocardial reperfusion injury. The pathophysiology of the process of reperfusion suggests the confluence multiple pathways. Recent studies have focused on the inflammatory response, which is considered to be the main mechanism during the process of myocardial ischemia-reperfusion injury and can cause cardiomyocyte apoptosis. Peroxisome proliferator-activated receptors gamma activated by endogenous ligands and exogenous ligand can de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 100 publications
1
3
0
Order By: Relevance
“…The locally released riskrelated molecular pattern initiates and triggers the NODlike receptor protein 3 inflammasome, and enhances the inflammatory response and cell death through activating caspase-1 (23). Many studies have shown that inhibition of the inflammatory response can reduce cardiomyocyte apoptosis in the pathological process of myocardial I/R injury (24). Our study found that Art treatment suppressed myocardial apoptosis.…”
Section: Discussionsupporting
confidence: 57%
“…The locally released riskrelated molecular pattern initiates and triggers the NODlike receptor protein 3 inflammasome, and enhances the inflammatory response and cell death through activating caspase-1 (23). Many studies have shown that inhibition of the inflammatory response can reduce cardiomyocyte apoptosis in the pathological process of myocardial I/R injury (24). Our study found that Art treatment suppressed myocardial apoptosis.…”
Section: Discussionsupporting
confidence: 57%
“…The incidence of coronary heart disease with acute myocardial infarction is increased worldwide now [2]. In the process of blood flow reperfusion, however, it leads to a large number of inflammatory cells aggregation in the myocardium of original ischaemia, serious damage to vascular endothelial function, obvious metabolic dysfunction, arrhythmia, myocardial apoptosis [3][4][5]. It is the main cause of serious cardiac complications even death after coronary revascularization and heart transplantation [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A summary of reported PPARγ ligands is provided in Table 1. GW1929 [16] Betulinic acid [17] SR-202 [18] Oxidized LDL [19] TZD *** NFκB [20] BADGE [21] EETs [22] FMOC-L-Leucine [23] Fetuin A [20] LG100641 [24] 15d-PGJ2 [25] INT131 [26] PD068235 [27] Azelaoyl phosphatidylcholine [28] Farglitazar (GI262570) [29] T0070907 [30] 9-oxoODE [31] S26948 [32] GW9662 [33] 13-oxoODE [34] AZ 242 [35] 15-HETE [36] LG100754 [37] 13-HODE [36] * Partial ligands of PPARγ such as telmisartan [38], Irbesartan [39], metaglidasen [40], and non-TZD partial agonist (nTZDpa) [41] are not included. ** poly-unsaturated FAs γ-linolenic (18:3), eicosatrienoic acid (C20:3), dihomoγ-linolenic (20:3), arachidonic acid (C20:4), and eicosapentaenoic acid (C20:5).…”
Section: Peroxisome Proliferator-activated Receptor-γmentioning
confidence: 99%